Factors Affecting the Implementation of Environmental Management Accounting Practices through New Institutional Sociology Perspective: A case of an Apparel Manufacturer in Sri Lanka - Nethsarani, K.A.T.; Samudrage, D.N. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2021)
The emergence of contemporary business environment and technologies, customer driven business perspective, and transparent and accountable business practices have led different stakeholders to demand information in relation to the management of the environment. Consequently, organizations tend to develop their strategies in line with achieving these financial and environmental performances. The apparel industry is one of the significant contributors in the Sri Lankan economy and it can be seen that Environmental Management Accounting (EMA) is often practiced in this industry. However, it is a matter of consideration for the real reason behind the adoption and implementation of Environmental Management Accounting Practices (EMAPs) in this industry. Accordingly, this study is focused on identifying the actual factors that have influenced a manufacturer in the apparel industry in Sri Lanka to adopt and implement EMAPs with the perspective of the New Institutional Sociology Theory. This study takes a case study approach. Therefore, one of the leading manufacturing companies in the apparel industry was selected as the case company. The primary data were collected through a semi-structured interview and questionnaire survey. The validity of findings was assessed through data triangulation. It was identified that the environmental cost accounting, environmentally induced capital expenditure and revenue are the mostly used EMAPs whereas the payback period method is often applied in the organization for investment appraisal activities. In terms of factors that have influenced to adopt and implement EMAPs through the Institutional Theoretical Perspective, it was found that coercive isomorphism was the most significant factor whereas the least influential factor was the normative isomorphism on the adoption and the implementation of the EMAPs in the organization. In terms of coercive isomorphism, the government regulations are the most influential force on this adoption and the implementation. Further, the study found some reasons behind the adoption of more Physical EMAPs (PEMAPs) than the Monetary EMAPs (MEMAPs) by the organization. The study contributes to minimize the gap by revealing the types of EMAPs that have been adopted and implemented and revealing the actual factors that have led to adopt and implement those practices in a manufacturer of the apparel industry.
Keywords: Environmental Management Accounting Practices, New Institutional Sociology Perspective, Apparel Manufacturer